A case study on radiate method in on-line method in cadastral adjustment / Nur Alia Amirudin - Amirudin, Nur Alia (2021)
Radiation method one of cadastral observation method where is suitable for locating boundary marks which are within a single tape length (from the location of plane table) and on-line method is a situation where a boundary marks are parallel towards other boundary marks. This method usually performed during the land title of property especially terrace house. However, there is an improvement when using these two methods in terms of geometry data checking during field observations since LSA only fulfil certain condition using these two methods. This paper highlight issues on how to apply radiation method and on-line method in cadastral survey observation method. In order to solve the aim of this study, there are three objectives need to be achieved which is to study the variations of impact when performing radiation in on-line method and to propose the new standard procedure relating to the issue given. The result of this study will be a new guideline for radiate method in on-line method and to find the suitability of using these two methods.